Uso de indicadores indigestíveis obtidos in situ e in vivo para determinar a digestibilidade de nutrientes em equinos - Oliveira, Katia de [UNESP]; Costa, C. [UNESP]; Bittar, Carla Maris Machado; Santos, Vanessa Pillon dos; Sá, J. C. [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The objective of this paper was to study the use of the internal indigestible cellulose (CELi) and lignin (LIGi) markers, obtained in situ or in vivo, to predict the apparent digestibility of nutrients in horses. Four castrated horses were utilized in a randomized blocks experimental design. Treatments consisted of different digestibility determination methodologies: total feces collection (TC) and use of CELi and LIGi internal markers obtained by the in situ (IS) incubation in bovine rumen and in vivo (IV) by the mobile nylon bag technique (MNBT) with horses, resulting in five treatments. The diet consisted exclusively of coast-cross hay and the average daily dry matter intake corresponded to 2.0% of the BW of the horses. The CELi-IV resulted in the best marker recuperation rate (100.31%), being similar to the control method; while the LIGi resulted in low recuperation rates (76.45%) for both techniques (P<0.05). The nutrients' digestibility coefficients were effectively predicted by CELi, obtained in situ or in vivo, with average values of 46.41, 48.16, 46.90, 47.92 and 45.51% for DM, organic matter, crude protein, neutral detergent fiber and crude energy, respectively. It can be concluded that CELi may be obtained in vivo by MNBT in horses to predict the nutrients' digestibility coefficients.

Objetivou-se estudar a viabilização dos indicadores internos, celulose (CELi) e lignina (LIGi) indigestíveis, obtidos pelas técnicas in situ e in vivo, para predizer a digestibilidade de nutrientes em equinos. Foram utilizados quatro cavalos castrados, por meio de delineamento em blocos ao acaso. Os tratamentos consistiram de metodologias de avaliação de digestibilidade, como a coleta total de fezes (CT) e o uso de indicadores internos, CELi e LIGi, obtidos pelas técnicas in situ (IS) na cavidade ruminal de bovinos e in vivo (IV) nos equinos, por meio da técnica do saco de náilon móvel (TSNM), totalizando cinco tratamentos. A ingestão diária de MS foi de 2,0% do peso vivo de feno de coast-cross. A CELi-IV promoveu a melhor taxa de recuperação do indicador, igualando-se à CT, em 100,31%, enquanto a LIGi resultou nas piores taxas, na média 76,45%, para ambas as técnicas (P<0,05). As estimativas dos coeficientes de digestibilidade dos nutrientes foram adequadamente preditas pela CELi, obtidos IS e IV em que os valores observados foram de 46,41, 48,16, 46,90, 47,92 e 45,51% para MS, MO, PB, FDN e EB, respectivamente. Concluiu-se que a CELi pode ser obtida in vivo por meio da TSNM em equinos, para predizer a digestibilidade de nutrientes.
The use of indigestible markers obtained in situ and in vivo to determine digestibility of nutrients in equine
Keywords: Cavalo; Indicador interno; Método indireto e metodologia de avaliação; Horse; Indirect method; Internal marker and evaluation methodology